Efektivitas Pengelolaan Dana Desa Pada Masa Pandemi Covid-19 (Studi Kasus Desa Krincing Kabupaten Magelang) - Nurjannah Rahayu Kistanti; Mayang Putri Didanti (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2025)
Direct Village Fund Cash Assistance (BLT DD) is a National Economic Recovery Program (PEN) intended for communities affected by the Covid-19 pandemic (Ministry of Finance, 2021). This research is descriptive quantitative research, and the method used in this research is the descriptive statistical analysis method and the AHP (Analytical Hierarchy Process). This research aims to determine the effectiveness of the BLT DD program in and analyze the characteristics of recipients of the BLT program in Krincing Village. The effectiveness measurements used to Makmur, (2011) which determine the success of this program are indicators of timeliness, target accuracy, and achievement of goals. The research results show that the implementation of the village fund policy for the Covid-19 pandemic is running quite effectively, although in its implementation there are several problems such as community confusion in submitting complaints, invalidity of families receiving mandates and the organizers' partiality or subjectives in determining potential recipients of direct assistance. Based on the results of the AHP analysis, the strategy that can be used to increase the effectiveness of the Krincing Village BLT DD program is a policy strategy to achieve objectives.